2012
DOI: 10.1097/mat.0b013e3182436817
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Placenta IV

Abstract: An extracorporeal artificial placenta would change the paradigm of treating extremely premature infants. We hypothesized that a venovenous extracorporeal life support (VV-ECLS) artificial placenta would maintain fetal circulation, hemodynamic stability, and adequate gas exchange for 24 hours. A near-term neonatal lamb model (130 days; term = 145 days) was used (n = 9). The right jugular vein was cannulated for VV-ECLS outflow, and an umbilical vein was used for inflow. The circuit included a peristaltic roller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Despite cannulation of the aorta via the umbilical artery, we could not solve the problem of persistent hypotension. We transitioned to a model of venovenous (VV) ECLS with jugular drainage and umbilical reinfusion and supported lambs for up to 92 hours [13, 16]. We found that this model of an AP provided adequate perfusion to the brain despite the ligation of one carotid artery for monitoring line placement [17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite cannulation of the aorta via the umbilical artery, we could not solve the problem of persistent hypotension. We transitioned to a model of venovenous (VV) ECLS with jugular drainage and umbilical reinfusion and supported lambs for up to 92 hours [13, 16]. We found that this model of an AP provided adequate perfusion to the brain despite the ligation of one carotid artery for monitoring line placement [17].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the AP stabilized hemodynamics and gas exchange, maintained fetal circulation, and provided cerebral perfusion for over 70h of support. This is a significant step forward from our previous series of five 24h survivors on TAPS and another advance towards clinical translation of this technology [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The most successful study described 3 week AV-ECLS support of 2 goat fetuses in 1993, but these results have not been reproduced nor have there been significant advances leading to clinical translation [8]. Despite limited initial success in our laboratory with AV-ECLS AP models, we made greater strides after transitioning to a pump-driven VV (venovenous)-ECLS AP preparation [9,10]. We reported a series of 5 near-term premature sheep that maintained hemodynamic stability and fetal gas exchange parameters for 24h using a VV-ECLS AP [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[46**] During these experiments sheep were delivered prematurely by Caesarean section and cannulated while on native placental support. Initially they were maintained in an artificial amniotic bath, but it was noted to become easily infected causing sepsis in sheep who lived >24hrs.…”
Section: The Artificial Placenta: Recent Advancesmentioning
confidence: 99%